COMPARISON OF EDUCATIONAL REFORMS IN GERMANY AND UZBEKISTAN (Scientific journal of the Fergana State University, 2025)
Nowadays, every society pays great attention to the development of the private education system, because it plays an important role in ensuring the stable socio-economic development of the country by purposeful formation of the next generation. Different countries have different approaches to the organization of education based on specific historical, cultural and social conditions. In the years of independence, based on the real demands of the economy and social life, great work was done and is being done to modernize the higher education system in our country, to introduce modern forms and technologies of teaching, and to improve specialization areas for training specialists. Decision No. PQ2909 of the President of the Republic of Uzbekistan dated April 20, 2017 "On measures for the further development of the higher education system" corresponds to the priority tasks of the fundamental improvement of the higher education system and the socio-economic development of our country in this case, it was adopted in order to fundamentally revise the content of personnel training, to create the necessary conditions for the training of highly qualified specialists at the level of international standards. In this decision, it is necessary to strengthen the professional skills of professors and teachers, to improve the qualifications of pedagogical staff, as well as to improve their qualifications at foreign partner higher educational institutions, to receive master's and doctoral studies, and to undergo retraining at the base higher educational institutions of our republic. and skill development was set as the main task in improving the quality and efficiency of education. A number of higher education institutions of the country have established cooperative relations with the leading scientific and educational institutions of the USA, Great Britain, France, Germany, Italy, the Netherlands, Russia, Japan, South Korea, China and other similar countries is important. In order to conduct a comparative study of lexical units related to the educational system, similarities and differences in the structure, organization, curricula and programs of educational institutions in Germany and Uzbekistan were first identified. The analysis of these two systems provides an in-depth understanding of the educational approaches and strategies adopted in the target countries, as well as an assessment of their effectiveness and relevance in achieving educational goals.